2011
DOI: 10.1210/en.2011-0004
|View full text |Cite
|
Sign up to set email alerts
|

Impaired CNS Leptin Action Is Implicated in Depression Associated with Obesity

Abstract: Recent epidemiological studies indicate that obesity increases the incidence of depression. We examined the implication of leptin for obesity-associated depression. Leptin induced antidepressive behavior in normal mice in a forced swimming test (FST), and leptin-overexpressing transgenic mice with hyperleptinemia exhibited more antidepressive behavior in the FST than nontransgenic mice. In contrast, leptin-deficient ob/ob mice showed more severe depressive behavior in the FST than normal mice, and leptin admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(184 citation statements)
references
References 41 publications
11
168
2
2
Order By: Relevance
“…Recently significant interest has arisen in possible interactions between central mood substrates and circuitries involved in metabolism (Gomez-Pinilla, 2008;Krishnan and Nestler, 2008;Kuperman et al, 2010;McBriar, 2006;Shao et al, 2008). More specifically, several neuropeptides with a clear role in metabolism, such as leptin, ghrelin, orexin, neuropeptide Yand urocortin 3, produce clear anti-depressant-like responses (Eaton et al, 2007;Heilig, 2004;Kuperman et al, 2010;Lu, 2007;Lutter et al, 2008;Yamada et al, 2011), whereas e.g. melanin-concentrating hormone and cholecystokinin evoke a pro-depressant-like phenotype in several rodent models (Becker et al, 2008;Georgescu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently significant interest has arisen in possible interactions between central mood substrates and circuitries involved in metabolism (Gomez-Pinilla, 2008;Krishnan and Nestler, 2008;Kuperman et al, 2010;McBriar, 2006;Shao et al, 2008). More specifically, several neuropeptides with a clear role in metabolism, such as leptin, ghrelin, orexin, neuropeptide Yand urocortin 3, produce clear anti-depressant-like responses (Eaton et al, 2007;Heilig, 2004;Kuperman et al, 2010;Lu, 2007;Lutter et al, 2008;Yamada et al, 2011), whereas e.g. melanin-concentrating hormone and cholecystokinin evoke a pro-depressant-like phenotype in several rodent models (Becker et al, 2008;Georgescu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians experience that the mood of a patient improves during weight restoration-potentially as a consequence of an increased leptin synthesis. Interestingly, leptin-deficient ob/ob mice show more severe depressive behavior in the forced swim test than normal mice, and leptin administration substantially ameliorates this depressive behavior [18].…”
mentioning
confidence: 99%
“…It was suggested that both leptin insufficiency and leptin resistance may contribute depressive status 72 . These findings are translated and further supported by several animal studies 73 including pharmacological experiments where leptin induced antidepressive-like behaviour in a forced swimming test, a commonly used test for evaluation of depressive-like phenotype in rodents 74 . Blood levels of another adipokine -adiponectin -were found to be reduced in Brazilian patients with major depression before antidepressant treatment.…”
Section: Depression and Metabolic Syndromementioning
confidence: 62%